TRACES OF SRIVIJAYA TRADE AND CULTURE: CERAMICS AND ANCIENT MONEY FOUND IN THE MUSI RIVER, PALEMBANG - Kabib Sholeh; Warto; Djono; Wahyu Rizki Andifani (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Srivijaya was the largest maritime kingdom in Southeast Asia that reached its peak in the 7th to 13th centuries AD. Its strategic position on international trade routes made it a center of economic and cultural exchange connecting East Asia, South Asia, and the Middle East. One of the evidences of Srivijaya's trade and cultural acculturation traces can be found on the Musi River, which functioned as the main route for distributing trade goods. This study uses historical methods, including heuristics (collection of sources), source criticism, interpretation, and historiography, to analyze archaeological findings in the form of ceramics and ancient money found in the Musi River, Palembang. The results of the study show that the ceramics found in the Musi River, Palembang come from various dynasties in China, such as the Tang Dynasty (618–907 AD), Song (960–1279 AD), and Yuan (1271–1368 AD), indicating close trade relations between Srivijaya and China. In addition, the discovery of ancient currencies, including gold, silver, and copper coins from local and Chinese sources, reveals that Srivijaya already had a currency-based economic system in its trade transactions. Through source criticism and analysis, it was found that the flow of trade on the Musi River not only had an impact on the economic development of Srivijaya, but also influenced the social and cultural aspects of its people, such as in art, belief systems, and daily life patterns. This study confirms that Srivijaya was not only a regional trade center, but also an important node in the global trade network that accelerated the process of cultural acculturation. Using historical methods, this study provides deeper insight into the dynamics of Srivijaya trade and culture, and enriches understanding of the role of the Palembang Musi River in the maritime history of the archipelago.